Systematic Literatur Review: Pengaruh Kepemimpinan Kepala Sekolah, Terhadap Kepuasan Kinerja Guru di Sekolah Dasar - Sri Susila (Yayasan Sembilan Pemuda Indonesia, 2025)
This research is a meta-analysis study aimed at evaluating the influence of school leadership on teachers’ performance and job satisfaction. This review includes 15 scientific articles published between 2021 and 2024. The method used is a literature study with a descriptive qualitative approach. The findings indicate that school leadership has a positive and significant impact on both teachers’ performance and job satisfaction. Additionally, other variables such as work motivation, compensation, organizational climate, and school culture also contribute to strengthening the relationship between school leadership and teachers’ work outcomes. These findings emphasize the importance of developing school leadership capacity to enhance professionalism and well-being among teachers in the educational environment. This study provides recommendations for policymakers and education stakeholders to focus on improving leadership in schools as a strategic step to create a more productive and satisfying work environment for teachers.